Aqueous extract from Chrysophyllum cainito bark exhibits embryonic toxicity in Danio rerio and negligible acute toxicity in adult Wistar rats - Doan, Hau Van; Sritangos, Pishyaporn; Weeranantanapan, Oratai; Chudapongse, Nuannoi (Archives of Biological Sciences, 2021)
Paper description: Chrysophyllum cainito is a widely used alternative antidiabetic medicine in many countries in Asia, and previous studies showed that C. cainito bark extract exerts antidiabetic, anti-inflammatory, proapoptotic and anticancer effects. Due to lack of toxicity assessment, acute toxicity of the aqueous C. cainito bark extract in the rat, and embryotoxicity in the zebrafish experimental model were examined. First evidence that the bark extract induces embryotoxicity in zebrafish at low concentrations and negligible acute toxicity in adult Wistar rats is provided. C. cainito bark extract should be cautiously applied in women during pregnancy. Abstract: Chrysophyllum cainito has been used as a traditional medicine to treat a wide range of diseases, but the toxicity profile of this plant remains unknown. This study aimed to evaluate the acute toxicity of the aqueous extract of C. cainito (CE) bark based on OECD guidelines in two different in vivo experimental models: acute single-dose oral toxicity in adult Wistar rats and the zebrafish embryo acute toxicity test. All concentrations of CE (500-4000 mg/kg) tested during a 14-day period in both male and female rats showed no effect on behavior, body weight, organ weights, biochemical and hematological parameters. In contrast, CE significantly delayed zebrafish embryo hatching and decreased embryo survival rates in a dose-dependent manner. Hatched larvae were notably sensitive to CE-induced toxicity compared to unhatched fish embryos. Acridine orange staining showed that CE induced apoptosis in the yolk sac region that is responsible for supplying nutrients to support larval growth and development. According to OECD guidelines, CE was identified as GHS category 5, a substance with low to no acute toxicity. However, as embryotoxicity was observed in zebrafish, CE use during pregnancy should be exercised with caution until further examination of its safety.